Heating Value Evaluation of Palm Oil Waste - Supeni, Eris Elianddy (2004)
The aim of this project is to evaluate the heating value of palm oil waste (POW).It is also concerned with the theory and method for determining heating value.The POW have high moisture contents (MC) which may affect the heating value.Therefore,this study also investigates the relationship between higher heating value (HHV) and MC. Calorimetry is the science of measuring heat based on the change in temperature that occurs during energy exchange between a reaction system and its environment.This exchange in energy can be measured using a thermally insulated container known as a bomb calorimeter. The experimentation part of this project mainly comprises on the calibration of the experimental set-up and arrangement and secondly the determination of POW’S HHV at full dry condition, as well as for different MC.Before conducting the tests on POW samples,the calibration test must be carried out firstly to identify whether the equivalent value of energy obtained is recommended by the manufacturer.Then, the remaining experiments will be proceeded further to satisfy the scope of the study. The POW which was fresh fibre and shell samples were collected from the Sri Ulu Langat, Dengkil, Selangor. The statistical analysis of t-test was applied to see whether all heating values of POW show significantly different between one to each other at fully dry.To verify all data sampling for POW at different MC,the Anova one-way test was used to see whether the heating values varied with the moisture contents.It is clearly being observed that higher heating value (HHV) is a function of moisture contents (MC). As conclusion,the aim of the study to evaluate the heating values of POW has been achieved